2013
DOI: 10.5152/tao.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Localization of Septal Deviation on the Success of Septoplasty using NOSE Scale

Abstract: Objective:To measure the effect of localization of septal deviation on the success of septoplasty using the-Nose Obstruction Symptom Evaluation (NOSE) scale in patients undergoing septoplasty and endoscopic reduction of inferior turbinates. Methods:Patients who attended Oltu Goverment Hospital ENT clinic with nasal septal deviation between March 2011 and June 2012 were included in this study. Patients who had paranasal sinus problems other than concha hypertrophy and revision cases were excluded from this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…11 Sisman et al reported no association between localization of the septal deviation and the NOSE score; however, there was a postoperative significant decrease in the NOSE score compared with the preoperative values. 12 Nasal obstruction is commonly observed ipsilateral to the side of the deviation; conversely, in some cases due to inferior conchal hypertrophy, the nasal obstruction can be observed on the contralateral side, known as paradoxical nasal obstruction. 4 There is no consensus on whether this hypertrophy requires treatment; and if so, which technique is to be used.…”
Section: Discussionmentioning
confidence: 99%
“…11 Sisman et al reported no association between localization of the septal deviation and the NOSE score; however, there was a postoperative significant decrease in the NOSE score compared with the preoperative values. 12 Nasal obstruction is commonly observed ipsilateral to the side of the deviation; conversely, in some cases due to inferior conchal hypertrophy, the nasal obstruction can be observed on the contralateral side, known as paradoxical nasal obstruction. 4 There is no consensus on whether this hypertrophy requires treatment; and if so, which technique is to be used.…”
Section: Discussionmentioning
confidence: 99%